2007
DOI: 10.1063/1.2795681
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic-ferromagnetic phase transition and magnetic properties of ultrathin CoFe∕Cu(110) films

Abstract: We present the results of a systematic investigation of the coverage-dependent magnetic response and anisotropy of ultrathin Co75Fe25∕Cu(110) films using the magneto-optic Kerr effect. A paramagnetic-ferromagnetic phase transition is found to occur at a critical thickness dc=4.0±0.25 ML. In the vicinity of dc, the paramagnetic susceptibility χ follows a power law with a critical exponent of γ=2.385±0.069 in excellent agreement with the theoretical value for a perfect two-dimensional geometric percolation phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…トンネル磁気抵抗(TMR)ヘッドや不揮発性磁気抵抗メモリ (MRAM)などの磁気応用デバイスの開発を目的として,FeCo 層と絶縁体層を用いた磁気トンネル接合(MTJ)に関する研究が 盛んに行われている.絶縁体層材料として,Al-O 非晶質 [1][2][3][4] , MgO 結晶 5-7) が用いられ,近年,SrTiO3結晶 [8][9][10] も注目されつつ ある.大きな磁気抵抗率を得るためには FeCo 層と絶縁体層との ヘテロ界面制御が重要である.計算機シミュレーションにより, MgO 結晶 11) もしくは SrTiO3結晶 12) を絶縁体層として用い, エピ タキシャル成長により形成した MTJ において,1000%を超える TMR 比が得られる可能性が示唆されており,磁性層/絶縁体層 のエピタキシャル構造の有用性が注目されている.また,磁気応 用デバイスの可能性検討では,薄膜材料の基本磁気特性を知る必 要があり,膜構造が制御されたエピタキシャル薄膜を用いて,結 晶磁気異方性エネルギーやダンピング定数などの検討も行われて いる 13,14) . これまで,塩化ナトリウム型(B1)構造を持つ MgO(a MgO = 0.4213 nm) 単結晶基板 [15][16][17] や閃亜鉛鉱型 (B3) 構造を持つ GaAs (a GaAs = 0.5653 nm)単結晶基板 [18][19][20][21] を用いてエピタキシャル FeCo 薄膜の作製が試みられ,磁気特性などが検討されている. また,単結晶基板上にヘテロエピタキシャル成長させた fcc(A1) 構造の Cu,Ag,Au 下地層 [22][23][24][25] や bcc(A2)構造の Cr,W 下地 層 26,27) を用いた FeCo 薄膜のエピタキシャル成長も試みられてい る.しかしながら,エピタキシャル薄膜成長は薄膜形成法,基板 材料や基板結晶方位,基板温度などの形成条件に敏感に影響され ることが知られているが 28,29) FeCo{200} poles observed for FeCo thin film grown on SrTiO3(100) substrate at 300 °C. The intensity is shown in a logarithmic scale.…”
Section: はじめにunclassified
“…トンネル磁気抵抗(TMR)ヘッドや不揮発性磁気抵抗メモリ (MRAM)などの磁気応用デバイスの開発を目的として,FeCo 層と絶縁体層を用いた磁気トンネル接合(MTJ)に関する研究が 盛んに行われている.絶縁体層材料として,Al-O 非晶質 [1][2][3][4] , MgO 結晶 5-7) が用いられ,近年,SrTiO3結晶 [8][9][10] も注目されつつ ある.大きな磁気抵抗率を得るためには FeCo 層と絶縁体層との ヘテロ界面制御が重要である.計算機シミュレーションにより, MgO 結晶 11) もしくは SrTiO3結晶 12) を絶縁体層として用い, エピ タキシャル成長により形成した MTJ において,1000%を超える TMR 比が得られる可能性が示唆されており,磁性層/絶縁体層 のエピタキシャル構造の有用性が注目されている.また,磁気応 用デバイスの可能性検討では,薄膜材料の基本磁気特性を知る必 要があり,膜構造が制御されたエピタキシャル薄膜を用いて,結 晶磁気異方性エネルギーやダンピング定数などの検討も行われて いる 13,14) . これまで,塩化ナトリウム型(B1)構造を持つ MgO(a MgO = 0.4213 nm) 単結晶基板 [15][16][17] や閃亜鉛鉱型 (B3) 構造を持つ GaAs (a GaAs = 0.5653 nm)単結晶基板 [18][19][20][21] を用いてエピタキシャル FeCo 薄膜の作製が試みられ,磁気特性などが検討されている. また,単結晶基板上にヘテロエピタキシャル成長させた fcc(A1) 構造の Cu,Ag,Au 下地層 [22][23][24][25] や bcc(A2)構造の Cr,W 下地 層 26,27) を用いた FeCo 薄膜のエピタキシャル成長も試みられてい る.しかしながら,エピタキシャル薄膜成長は薄膜形成法,基板 材料や基板結晶方位,基板温度などの形成条件に敏感に影響され ることが知られているが 28,29) FeCo{200} poles observed for FeCo thin film grown on SrTiO3(100) substrate at 300 °C. The intensity is shown in a logarithmic scale.…”
Section: はじめにunclassified
“…17 Figure 4(c) shows the in-plane angular dependence of H RES . K€ upper et al 21 reported that single crystalline Co-Fe system can present quite strong biaxial anisotropy. In the present experiment, although the Co 75 Fe 25 films are polycrystalline, an uniaxial anisotropy seems to exist, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The onset of ferromagnetism was observed to occur at a critical thickness of d C ¼4.0 70.25 ML and the paramagnetic susceptibility, w, follows a power law with a critical exponent of g¼2.38570.069, in excellent agreement with the theoretical value for a two-dimensional geometric percolation phase transition [39]. The effects of O 2 and H 2 dosing on the magnetism of Co 75 Fe 25 films has also been studied.…”
Section: Introductionmentioning
confidence: 83%
“…Any such ultrathin film that exhibits both cubic and uniaxial anisotropies, and whose anisotropy contributions favour different easy axis directions should allow the easy axis to rotate in-plane between the two, depending on the ratio of the two anisotropies. As has already been shown, the unstable fcc phase of Co 75 Fe 25 can be initially stabilised by epitaxial growth on Cu (1 1 0), creating an uniquely orientated system, which allows both the cubic and uniaxial anisotropy contributions to be distinguished [39]. The different symmetry axes that exist in this surface lead to a competition between the two anisotropies.…”
Section: Introductionmentioning
confidence: 90%